Identifikasi Mikonsepi Siswa Kelas X Pada Materi Struktur Atom - Herdien, Rahmah Aprillia (Journal of Chemistry Sciences and Education, 2024)
Chemistry is a science that is not easily understood by students. The main obstacle to understanding chemical concepts is understanding at the sub-microscopic level which is often overlooked and understanding is only emphasized at the macroscopic and symbolic level. The atomic structure is the basic material of chemistry which often gives rise to misconceptions because it has an abstract and difficult concept. If during learning students experience misconceptions about one of the basic concepts, then the possibility of misconceptions arising will be greater for more complex concepts. Therefore, researchers conducted research aimed at identifying misconceptions of class X students at SMAN 1 Parung regarding Atomic Structure material. The research method used is quantitative descriptive. The research subjects were 36 class X students at SMAN 1 Parung who were determined based on purposive sampling techniques. The research instrument used was a four-tier Multiple Choice diagnostic test question, where students' answers were then analyzed and categorized based on level of understanding. The research results showed that there were 30.67% misconceptions (low category). Misconceptions in the five sub-concepts of Atomic Structure, namely the development of atomic theory according to Dalton, Thomson, Rutherford, Bohr, and quantum mechanics (27.86%); Basic particles (Protons, Electrons and Neutrons) and the process of their discovery (35.00%); Element Notation (34.29%); Isotopes, Isotones, and Isobars (30.00%); Electron Configuration (26.67%). It is hoped that the results of identifying student misconceptions can help handle student misconceptions from an early age so that they do not hinder students in learning.